Creep behaviour of donax grandis fibre-reinforced polymer composites in hygric condition - Razali, N.T (Universiti Malaysia Sarawak, UNIMAS, 2006)
The compressive creep test have been conducted for Donax Grandis fibre-reinforced polymer composite in 10% and 20% fibre volume fraction in hygric condition. This experimental study was taken to determine the effect of creep behaviour of Donax Grandis fibre-reinforced polymer composite by applying various load at hygric condition.